2015
DOI: 10.1111/desc.12356
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between phonological awareness, morphological awareness and Chinese literacy skills: evidence from an 8‐year longitudinal study

Abstract: The present study reported data on phonological awareness, morphological awareness, and Chinese literacy skills of 294 children from an 8-year longitudinal study. Results showed that mainland Chinese children's preliterate syllable awareness at ages 4 to 6 years uniquely predicted post-literate morphological awareness at ages 7 to 10 years. Preliterate syllable awareness directly contributed to character reading and writing at age 11 years, while post-literate phonemic awareness predicted only character readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
83
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 52 publications
(86 reference statements)
11
83
0
1
Order By: Relevance
“…This path indicated that children from more educated and advantaged parents might have greater vocabulary skills, which would use their understanding of the meaning of the words better to facilitate their morphological awareness (Cheng et al, 2015) and in turn, may lead to high level reading comprehension (Tong et al, 2009; Pan et al, 2016). In other words, vocabulary is a mediator between SES and morphological awareness, and morphological awareness is a mediator between vocabulary knowledge and reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This path indicated that children from more educated and advantaged parents might have greater vocabulary skills, which would use their understanding of the meaning of the words better to facilitate their morphological awareness (Cheng et al, 2015) and in turn, may lead to high level reading comprehension (Tong et al, 2009; Pan et al, 2016). In other words, vocabulary is a mediator between SES and morphological awareness, and morphological awareness is a mediator between vocabulary knowledge and reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the psychological mechanism by which the effects of SES are manifested in children’s reading comprehension are not well understood. Thus, the purpose of the current study was to explore further the relationship between SES and reading comprehension – focusing on the roles of vocabulary knowledge and morphological awareness, as these appear to have unique influences in Chinese reading development (Song et al, 2015; Pan et al, 2016; Cheng et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, morphological awareness plays a fundamental role in mastering decoding, reading fluency, and comprehension (Deacon and Kirby, 2004; Kuo and Anderson, 2006; Tong et al, 2011; Kirby et al, 2012; Deacon et al, 2014; Muroya et al, 2017) and orthographic spelling (Deacon and Kirby, 2004; Deacon and Bryant, 2005, 2006; Desrochers et al, 2017) across orthographies (Wei et al, 2014; Rothou and Padeliadu, 2015; Grigorakis and Manolitsis, 2016; Pan et al, 2016; Vaknin-Nusbaum et al, 2016a,b; Muroya et al, 2017). Morphological awareness refers to (a) an explicit understanding of morphological relations between word forms and meanings, such as grammatical inflection and productive derivation, and (b) the ability to manipulate the morphological structure of words (Carlisle, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, using latent variable modeling in Chinese, Pan et al (2016) found that pre-literate syllable and morphological awareness predicted character reading, reading fluency, reading comprehension, and writing at the age of 11 years, beyond any effects of phonological awareness, but only indirectly, that is, through post-literate morphological awareness assessed at the ages of 7–10 years.…”
Section: Introductionmentioning
confidence: 99%